2016
DOI: 10.1155/2016/2931985
|View full text |Cite
|
Sign up to set email alerts
|

The Burden of NAFLD and Its Characteristics in a Nationwide Population with Type 2 Diabetes

Abstract: Objective. We studied the prevalence of nonalcoholic fatty liver disease (NAFLD) and its clinical correlates in a population of patients with type 2 diabetes mellitus (T2DM). Methods. Clinical data of 94,577 T2DM patients were retrieved from 160 diabetes clinics in Italy in a standardized format and centrally analyzed anonymously. After exclusion of 5967 cases (high or uncertain alcohol intake), in 38,880 the Fatty Liver Index (FLI) was used as a proxy for the diagnosis of NAFLD. Factors associated with FLI as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 32 publications
3
61
1
1
Order By: Relevance
“…Other complications of diabetes include liver diseases that are mainly caused by insulin resistance and oxidative stress (Bouderba et al ., ). Two hepatic complications are largely present in patients with diabetes: (i) concomitant autoimmune hepatitis (Matsumoto et al ., ) and (ii) NAFLD (Forlani et al ., ). A study of 118 diabetic patients found a prevalence of 24.5% of concomitant autoimmune hepatitis in diabetic patients (Matsumoto et al ., ).…”
Section: Hepatopathymentioning
confidence: 97%
“…Other complications of diabetes include liver diseases that are mainly caused by insulin resistance and oxidative stress (Bouderba et al ., ). Two hepatic complications are largely present in patients with diabetes: (i) concomitant autoimmune hepatitis (Matsumoto et al ., ) and (ii) NAFLD (Forlani et al ., ). A study of 118 diabetic patients found a prevalence of 24.5% of concomitant autoimmune hepatitis in diabetic patients (Matsumoto et al ., ).…”
Section: Hepatopathymentioning
confidence: 97%
“…Individuals with NAFLD have a ve times higher risk of developing diabetes [18,19]. The association between NAFLD and type 2 diabetes mellitus can be explained through insulin resistance, dyslipidemia, and accumulation of liver triglyceride in NAFLD and β-cell defect in type 2 diabetes mellitus [20].…”
Section: Study Subject Characteristicsmentioning
confidence: 99%
“…Most NAFLD patients have metabolic syndrome that refers to the metabolic disorder of protein, fat and carbohydrate in the body, causing the occurrence of hyperlipidemia, hyperglycemia and obesity. It is even closely associated with atherosclerotic cardio-cerebrovascular disease and extrahepatic malignant carcinoma (13,14). NAFLD is regarded as a disease that interacts with various diseases, not an isolated disease.…”
Section: Discussionmentioning
confidence: 99%